Performance evaluation of magnetic anion exchange resin removing fluoride. Issue 6 (28th July 2015) - Li, Qiang; Wang, Baijun; Li, Wentao; Wang, Cheng; Zhou, Qing; Shuang, Chendong; Li, Aimin
Abstract: BACKGROUND: Fluoride above a permissible level in drinking water has serious health effects on human beings. In this study, magnetic anion exchange resin, NDMP, was used to remove fluoride under different conditions and its defluoridation performance was compared with that of commercial D201 resin. RESULTS: NDMP had favourable adsorption capacity for fluoride at pH 5.0 to 9.0. Coexisting anions generated competition adsorption towards fluoride and the different competition influence ordering followed the sequence SO4 2 − > Cl − > NO3 − > HCO3 − . The existence of HA did not have a negative effect on fluoride adsorption under 40 mg L −1 of HA solution. The pseudo‐first‐order kinetic model fitted better for fluoride adsorption by both resins. The adsorption process was fitted better by the Langmuir model with a maximum fluoride adsorption capacity (13.5 mg g −1 ), indicating that the interaction between fluoride and NDMP resin was a homogeneous process. The negative values of Δ G° and Δ H° revealed that the adsorption was a spontaneous and exothermic reaction. Regenerated NDMP recovers adsorption performance without any loss. CONCLUSIONS: High adsorption and regeneration performance suggest that NDMP can be used as an effective and reusable defluoridation adsorbent. © 2015 Society of Chemical Industry